Spontaneous Nystagmus in the Dark in an Infantile Nystagmus Patient May Represent Negative Optokinetic Afternystagmus - Lin, Ting-Feng; Gerth-Kahlert, Christina; Hanson, James V. M.; Straumann, Dominik; Huang, Melody Ying-Yu (Frontiers in Neurology, 2018)
Abnormal projection of the optic nerves to the wrong cerebral hemisphere transforms the optokinetic system from its usual negative feedback loop to a positive feedback loop with characteristic ocular motor instabilities including directional reversal of the optokinetic nystagmus (OKN) and spontaneous nystagmus, which are common features of infantile nystagmus syndrome (INS). Visual input plays a critical role in INS linked to an underlying optic nerve misprojection such as that often seen in albinism. However, spontaneous nystagmus often continues in darkness, making the visual, sensory-driven etiology questionable. We propose that sensorimotor adaptation during the constant nystagmus of patients in the light could account for continuing nystagmus in the dark. The OKN is a stereotyped reflexive eye movement in response to motion in the surround and serves to stabilize the visual image on the retina, allowing high resolution vision. Robust negative optokinetic afternystagmus (negative OKAN), referring to the continuous nystagmus in the dark with opposite beating direction of the preceding OKN, has been identified in various non-foveated animals. In humans, a robust afternystagmus in the same direction as previous smooth pursuit movements (the eye’s continuous tracking and foveation of a moving target) induced by visual stimuli has been known to commonly mask negative OKAN. Some INS patients are often associated with ocular hypopigmentation, foveal hypoplasia, and compromised smooth pursuit. We identified an INS case with negative OKAN in the dark, in contrast to the positive afternystagmus in healthy subjects. We hypothesize that spontaneous nystagmus in the dark in INS patients may be attributable to sensory adaptation in the optokinetic system after a sustained period of spontaneous nystagmus with directional visual input in light.